Revision of Platycheirus Lepeletier and Serville (Diptera: Syrphidae) in the Nearctic north of Mexico - Young, Andrew D.; Marshall, Stephen A.; Skevington, Jeffrey H. (Zootaxa, 2016)
The 75 Nearctic species of Platycheirus Lepeletier and Serville found north of Mexico are revised, including five species new to North America: Platycheirus alpigenus Barkalov and Nielsen, Platycheirus brunnifrons Nielsen, Platycheirus clausseni Nielsen, Platycheirus speighti Doczkal, Stuke & Goeldlin, and Platycheirus splendidus Rotheray. Platycheirus rufimaculatus Vockeroth, Melanostoma willistoni Goot, and Melanostoma concinnus Snow are recognized as junior synonyms of Platycheirus pictipes (Bigot). Melanostoma carinata Curran is recognized as a junior synonym of Platycheirus chilosia (Curran). Melanostoma atra Curran is recognized as a junior synonym of Platycheirus luteipennis (Curran). Platycheirus holarcticus Vockeroth is recognized as a junior synonym of Syrphus naso Walker. Platycheirus trichopus (Thomson) is resurrected and represents what was previously considered the western population of Platycheirus obscurus (Say). One new species, Platycheirus neoperpallidus Young sp. nov., is described. Females of 26 species are described for the first time, and an illustrated key to Nearctic Platycheirus is presented. DNA barcode data are presented for 60 Nearctic species and a COI gene tree of all available world Platycheirus species, as well as morphological and combined morphological/COI phylogenetic analyses of the Platycheirus albimanus species group are presented and discussed.